S100A8 Mediating TLR4/NF‐κB Axis Activation to Inhibit Diabetic Foot Healing in Bacterial Colonization - Qi Wang; Tong Sun; YanFei Xu; Li Zhang; Jiao Li; Lei Guo (The Journal of Gene Medicine, 2026)
ABSTRACT Background Diabetic foot ulcers (DFUs) represent a severe complication of diabetes, with persistent nonhealing closely associated with bacterial colonization and excessive inflammation. S100A8 participates in immune regulation, but its mechanism in DFU healing remains unclear. This study aimed to investigate whether S100A8 regulates the DFU healing process via the TLR4/NF‐κB pathway. Methods This study collected clinical DFU and normal tissue samples to analyze the relationship between S100A8 expression and healing. HaCaT and THP‐1 cells were stimulated with high glucose/inflammatory factors to observe changes in S100A8 expression. Cells were treated with rS100A8 and pathway inhibitors to assess TLR4/NF‐κB pathway activity, inflammatory cytokine secretion, cellular function, and antimicrobial peptide expression. A diabetic DFU mouse model was established to evaluate the effects of S100A8 neutralizing antibodies on wound healing, histopathology, bacterial load, and signaling pathways. Results Clinical and experimental studies indicate that S100A8 expression is significantly elevated in DFU lesions and correlates with impaired healing. High glucose synergistically induced high S100A8 expression in keratinocytes and macrophages within the inflammatory microenvironment. Mechanistically, S100A8 activates the TLR4/NF‐κB pathway in a dose‐dependent manner, promoting IκBα phosphorylation and degradation along with p65 nuclear translocation. This enhances proinflammatory factor release while simultaneously inhibiting keratinocyte migration and proliferation, suppressing antimicrobial peptide expression, and increasing bacterial adhesion. Animal studies confirm that topical application of S100A8 neutralizing antibodies suppresses TLR4/NF‐κB pathway activation, reduces inflammation and bacterial load, and accelerates wound healing. Conclusion S100A8 delays DFU healing by exacerbating inflammation, impeding cellular repair, and disrupting the antimicrobial barrier through activation of the TLR4/NF‐κB signaling axis. Targeted inhibition of S100A8 effectively ameliorates this pathological process, providing a novel therapeutic target and theoretical basis for DFU treatment.